Research progress on the mechanisms underlying poultry immune regulation by plant polysaccharides - Zhao, Ruo-Han; Yang, Fang-Xiao; Bai, Yi-Cheng; Zhao, Jing-Ying; Hu, Mei; Zhang, Xin-Yan; Dou, Teng-Fei; Jia, Jun-Jing (Frontiers in Veterinary Science, 2023)
In recent years, increasing interest has focused on natural components extracted from plants, among which plant polysaccharides have been highlighted because of their various biological activities. Plant polysaccharides are natural immunomodulators that can promote the growth of immune organs, activate immune cells and the complement system, and release cytokines. As a green feed additive, plant polysaccharides can not only relieve stress and enhance the immunity and disease resistance of poultry but also regulate the balance of intestinal microorganisms. This paper reviews the immunomodulatory effects and molecular mechanisms of different plant polysaccharides (Atractylodes macrocephala Koidz polysaccharide, Astragalus polysaccharides, Taishan Pinus massoniana pollen polysaccharide, and alfalfa polysaccharide) in poultry. Current research results reveal that plant polysaccharides have potential uses as therapeutic agents for poultry immune abnormalities and related diseases.